Conductive polymer composition and use thereof

By using a conductive polymer composition of polythiophene, nanostructured materials, polyglycerol or sugar alcohol and solvent in a specific ratio, coating and drying are carried out to form a conductive polymer film, an electrolytic capacitor with low ESR characteristics is prepared, which solves the problem of insufficient ESR characteristics in the prior art and meets the requirements of high speed and high frequency of electronic devices.

CN123036343APending Publication Date: 2026-11-03TOSOH CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580024530.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-01
Filing Date
2025-03-07
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

The ESR characteristics of existing conductive polymer capacitors cannot be sufficiently improved, failing to meet the demands of high-speed and high-frequency electronic devices.

Method used

An electrolytic capacitor is prepared by using a conductive polymer composition containing a specific ratio of polythiophene, nanostructured materials, polyglycerol or sugar alcohol and solvent, which is coated and dried to form a conductive polymer film that covers the surface of a dielectric oxide film.

Benefits of technology

It provides electrolytic capacitors with long life, high capacitance and low ESR characteristics, solving the problem of insufficient ESR characteristics in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036343A_ABST
    Figure CN123036343A_ABST
Patent Text Reader

Abstract

The present application provides a conductive polymer composition that can form an electrolytic capacitor having excellent low ESR characteristics. The conductive polymer composition comprises: 0.01 to 10 mass% of a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.001 to 10 mass% of a nanostructured material (B), 1 to 50 mass% of at least one selected from the group consisting of a polyglycerol and a sugar alcohol (C), and a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to conductive polymer compositions, conductive polymer films obtained by drying the conductive polymer compositions, and their uses. Background Technology

[0002] As a type of electrolytic capacitor, there is a known conductive polymer capacitor, which is a capacitor in which conductive polymers are used as electrolytes.

[0003] As a raw material for manufacturing such conductive polymer capacitors, conductive polymer compositions comprising self-doped polythiophene conductive polymers and carbon materials have been reported (e.g., Patent Document 1).

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-142739 Summary of the Invention

[0007] The problem that the invention aims to solve

[0008] The problem that electrolytic capacitors made using existing, known conductive polymer compositions cannot adequately improve ESR characteristics is becoming increasingly apparent.

[0009] Problem Solving Methods

[0010] A conductive polymer composition comprising:

[0011] Polythiophene (A) 0.01~10% by mass containing at least one structural unit selected from the structural units represented by the following general formula (1) and the structural units represented by the following general formula (2).

[0012] Nanostructured materials (B) 0.001~10% by mass

[0013] Selected from at least one of polyglycerol and sugar alcohols (C) 1-50% by mass, and

[0014] solvent,

[0015] [Chemical Formula 1]

[0016]

[0017] In the above general formula (1), M + In general formulas (1) and (2) above, R represents an organic group having a total number of 1 to 18 carbon atoms having at least one substituent selected from sulfonic acid group and phosphonic acid group.

[0018] The effects of the invention

[0019] According to one aspect of the present invention, an electrolytic capacitor exhibiting lower ESR characteristics can be provided. Detailed Implementation

[0020] The following describes one embodiment of the present invention in detail. It should be noted that, unless otherwise specified, in this specification, "A~B" representing a numerical range means "A or more and B or less".

[0021] Regarding electrolytic capacitors, with the increasing speed and frequency of electronic devices using them, there is a strong demand for long lifespan, high capacitance, and low ESR characteristics.

[0022] Based on these requirements, the conductive polymer composition of this embodiment can provide an electrolytic capacitor exhibiting excellent low ESR characteristics, which is not easily conceived according to the prior art.

[0023] It should be noted that this embodiment exhibits a significant effect in preventing the dissolution of the conductive polymer film within the electrolytic capacitor by possessing properties not found in conventionally known conductive polymer compositions. This effect helps to solve the problem of providing electrolytic capacitors exhibiting excellent low ESR characteristics.

[0024] In addition, this embodiment relates to a method for manufacturing a conductive polymer film, which includes a step of coating the above-mentioned conductive polymer composition onto a substrate and drying it.

[0025] In addition, this embodiment relates to a method for manufacturing an electrolytic capacitor, which includes a step of covering the surface of the dielectric oxide film of an anode body on which a dielectric oxide film is formed with the above-described conductive polymer composition and then heating and drying it.

[0026] In addition, this embodiment relates to an electrolytic capacitor having an anode body manufactured by the above-described manufacturing method and coated with the above-described conductive polymer composition.

[0027] According to this embodiment, a conductive polymer composition can be provided for manufacturing electrolytic capacitors that can maintain high capacitance and low ESR characteristics for a long time.

[0028] It should be noted that, in this specification, "electrolytic capacitor" refers to a capacitor containing a dielectric layer made of an oxide film of metal (e.g., aluminum), including solid electrolytic capacitors and hybrid capacitors. Specifically, in this specification, a solid electrolytic capacitor refers to a capacitor whose electrolyte is a solid. Furthermore, in this specification, a hybrid capacitor refers to a capacitor whose electrolyte is a mixed electrolyte formed by fusing conductive polymers with an electrolyte solution.

[0029] It should be noted that in this specification, "solid electrolytic capacitor" is sometimes referred to as "solid electrolytic capacitor element", and "hybrid capacitor" is sometimes referred to as "hybrid capacitor element".

[0030] This embodiment relates to a conductive polymer composition comprising: 0.01-10% by mass of polythiophene (A), 0.001-10% by mass of nanostructure material (B), 1-50% by mass of at least one selected from polyglycerol and sugar alcohol, and a solvent.

[0031] [Chemical Formula 2]

[0032]

[0033] In the above general formula (1), M + Represents a hydrogen ion. In the above general formulas (1) and (2), R represents an organic group having a total carbon number of 1 to 18, having at least one substituent selected from sulfonic acid and phosphonic acid groups.

[0034] In the above general formulas (1) and (2), R represents an organic group having a total number of 1 to 18 carbon atoms having at least one substituent selected from sulfonic acid group and phosphonic acid group.

[0035] The organic groups with a total carbon number of 1 to 18 mentioned above are not particularly limited, and examples include: methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, hexyl, isohexyl, heptyl, octyl, 2-ethylhexyl, nonyl, decyl, methoxymethyl, ethoxymethyl, propoxymethyl, isopropoxymethyl, butoxymethyl, isobutoxymethyl, tert-butoxymethyl, hexoxymethyl, isohexoxymethyl, heptoxymethyl, or octoxymethyl, etc.

[0036] The organic group having a total carbon number of 1 to 18 and having at least one substituent selected from sulfonic acid group and phosphonic acid group is not particularly limited, and examples include: methyl sulfonic acid, methyl phosphonic acid, 2-ethyl sulfonic acid, 2-ethyl phosphonic acid, 3-propyl sulfonic acid, 3-propyl phosphonic acid, 2-propyl sulfonic acid, 2-propyl phosphonic acid, 4-butyl sulfonic acid, 4-butyl phosphonic acid, 3-butyl sulfonic acid, 3-butyl phosphonic acid, 6-hexyl sulfonic acid, 6-hexyl phosphonic acid, 5-hexyl sulfonic acid, 5-phosphonic acid Hexyl, sulfonate methoxymethyl, phosphonate methoxymethyl, 2-sulfonate ethoxymethyl, 2-phosphonate ethoxymethyl, 3-sulfonate propoxymethyl, 3-phosphonate propoxymethyl, 2-sulfonate propoxymethyl, 2-phosphonate propoxymethyl, 4-sulfonate butoxymethyl, 4-phosphonate butoxymethyl, 3-sulfonate butoxymethyl, 3-phosphonate butoxymethyl, 6-sulfonate hexoxymethyl, 6-phosphonate hexoxymethyl, 5-sulfonate hexoxymethyl or 5-phosphonate hexoxymethyl, etc.

[0037] The structural unit represented by the above general formula (2) represents the doping state of the structural unit represented by the above general formula (1).

[0038] Regarding the aforementioned polythiophene (A), from the perspective of providing an electrolytic capacitor exhibiting lower ESR characteristics, it is preferable to have polythiophene (A') comprising at least one structural unit selected from the structural units represented by the following general formula (1') and the following general formula (2'), or to have polythiophene (A'') comprising at least one structural unit selected from the structural units represented by the following general formula (1'') and the following general formula (2'').

[0039] [Chemical Formula 3]

[0040]

[0041] In general formulas (1') and (2'), R 2 This represents a hydrogen atom, a methyl group, an ethyl group, or a straight-chain or branched alkyl group or fluorine atom with 3 to 6 carbon atoms; m represents an integer from 1 to 10; and n represents 0 or 1.

[0042] In the above general formulas (1') and (2'), there is no particular limitation on the straight-chain or branched alkyl group having 3 to 6 carbon atoms. Examples include: n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, n-hexyl, 2-ethylbutyl, or cyclohexyl.

[0043] In the above general formulas (1') and (2'), regarding R 2 From the perspective of film-forming properties, hydrogen atoms, methyl, ethyl or fluorine atoms are preferred.

[0044] In the above general formulas (1') and (2'), m represents an integer from 1 to 10. From the perspective of film-forming properties, it is preferably an integer from 1 to 6, more preferably an integer from 1 to 4, and even more preferably 2 or 3.

[0045] In the above general formulas (1') and (2'), n represents 0 or 1. From the perspective of excellent conductivity, n is preferably 1.

[0046] The structural unit represented by the above general formula (2') represents the doping state of the structural unit represented by the above general formula (1').

[0047] [Chemical Formula 4]

[0048]

[0049] In the above general formula (1''), M + Represents the hydrogen ion. In the above general formulas (1'') and (2''), R 3 Each time it appears, it independently represents a hydrogen atom, a straight-chain or branched alkyl group or halogen atom with 1 to 6 carbon atoms. R 4 This refers to a straight-chain or branched alkyl group having 1 to 6 hydrogen or carbon atoms. p represents 0 or 1, q represents an integer from 0 to 6, and r represents 0 or 1.

[0050] R in the above general formulas (1'') and (2'') 3 It represents hydrogen atoms, and straight-chain or branched alkyl or halogen atoms with 1 to 6 carbon atoms.

[0051] Examples of straight-chain or branched alkyl groups having 1 to 6 carbon atoms include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, n-hexyl, 2-ethylbutyl, or cyclohexyl.

[0052] Examples of halogen atoms mentioned above include fluorine atoms, chlorine atoms, or bromine atoms.

[0053] Regarding the R mentioned above 3 From the perspective of providing electrolytic capacitors exhibiting lower ESR characteristics, hydrogen atoms, methyl, ethyl or fluorine atoms are preferred, hydrogen atoms or methyl atoms are more preferred, and hydrogen atoms are even more preferred.

[0054] R in the above general formulas (1'') and (2'') 4 Represents a straight-chain or branched alkyl group having 1 to 6 hydrogen atoms or carbon atoms.

[0055] Examples of straight-chain or branched alkyl groups having 1 to 6 carbon atoms include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, n-hexyl, 2-ethylbutyl, or cyclohexyl.

[0056] Regarding the R mentioned above 4 From the perspective of providing electrolytic capacitors exhibiting lower ESR characteristics, hydrogen atoms, methyl or ethyl atoms are preferred, and hydrogen atoms are more preferred.

[0057] In the above general formulas (1'') and (2''), q represents an integer from 0 to 6, and from the perspective of providing electrolytic capacitors that exhibit lower ESR characteristics, q is preferred to be 0.

[0058] In the above general formulas (1'') and (2''), r represents 0 or 1, and from the perspective of providing electrolytic capacitors exhibiting lower ESR characteristics, 0 is preferred.

[0059] The structural unit represented by the above general formula (2'') represents the doping state of the structural unit represented by the above formula (1'').

[0060] Dopants that induce insulator-metal transfer due to doping are classified as acceptors and donors. Acceptors, by doping into the vicinity of the polymer chain of a conductive polymer, steal π electrons from the conjugated system of the main chain. As a result, positive charges (holes) are injected into the main chain, hence they are also called p-type dopants. Conversely, donors, on the other hand, donate electrons to the conjugated system of the main chain, thereby allowing these electrons to move within the conjugated system, hence they are also called n-type dopants.

[0061] The dopant in this embodiment is a sulfonyl or sulfonate group covalently bonded within the polymer molecule, and is a p-type dopant. Polymers that exhibit conductivity without the addition of external dopant are called self-doped polymers.

[0062] The polythiophene (A) of this embodiment can be a product available on the market, or it can be a polythiophene manufactured based on generally known methods.

[0063] In this embodiment, the conductivity of polythiophene (A) is not particularly limited, but it is preferably 10 S / cm or more in terms of conductivity in the film state.

[0064] It should be noted that the polythiophene (A) in this embodiment can also be a product synthesized based on publicly known information.

[0065] In the conductive polymer composition of this embodiment, regarding the content of polythiophene (A) containing at least one structural unit selected from the structural units represented by general formula (1) and general formula (2), the total amount of the conductive polymer composition is set to 100% by mass, characterized by 0.01 to 10% by mass, and preferably 0.05 to 8% by mass, more preferably 0.1 to 7% by mass, from the viewpoint of being able to provide an electrolytic capacitor with excellent low ESR.

[0066] The nanostructure material (B) is not particularly limited, but is preferably selected from at least one of cellulose nanofibers, single-layer carbon nanotubes, double-layer carbon nanotubes and multilayer carbon nanotubes. From the perspective of providing an electrolytic capacitor with excellent low ESR, cellulose nanofibers or single-layer carbon nanotubes are more preferred.

[0067] The diameter of the single-layer, double-layer, or multi-layer carbon nanotubes described above is not particularly limited, and can be, for example, less than 20 nm, preferably less than 10 nm, and more preferably less than 5 nm. It should be noted that there is no particular limitation on the lower limit of the diameter of the single-layer, double-layer, or multi-layer carbon nanotubes, and can be, for example, greater than 0.4 nm or 0.5 nm.

[0068] Regarding such nanostructured material (B), commercially available products can be used directly, or products prepared separately using known methods can be used. It should be noted that, from a stability perspective, nanostructured material (B) is more commonly sold in the form of a water-dispersible agent. Regarding the composition of this invention, it can be prepared directly using a water-dispersible agent of nanostructured material (B), or it can be prepared using a material obtained by separately desolvating and purifying the water-dispersible agent of nanostructured material (B).

[0069] In the conductive polymer composition of this embodiment, the content of the above-mentioned nanostructure material (B) is set to 100% by mass, and is 0.001 to 10% by mass. From the perspective of providing an electrolytic capacitor with excellent low ESR, it is more preferably 0.01 to 7% by mass, more preferably 0.01 to 5% by mass, and particularly preferably 0.05 to 3% by mass.

[0070] From the perspective of providing an electrolytic capacitor with excellent low ESR, the content of the nanostructure material (B) is preferably 0.01 to 7 parts by mass, more preferably 0.01 to 5 parts by mass, and particularly preferably 0.05 to 3 parts by mass, relative to 1 part by mass of polythiophene (A).

[0071] The polyglycerol mentioned above refers to a substance having a structure composed of multiple glycerols polymerized together, without particular limitation. Examples include diglycerol, triglycerol, tetraglycerol, or decaglycerol.

[0072] The sugar alcohols mentioned above are not particularly limited, and examples include erythritol, glycerol, lactitol, maltitol, xylitol, arabinitol, mannitol, and sorbitol. In this embodiment, one type of sugar alcohol may be used alone, or two or more may be used in combination. It should be noted that commercially available sugar alcohols may be used directly, or sugar alcohols manufactured using generally known methods may be used.

[0073] Regarding the above-mentioned selection of at least one of polyglycerol and sugar alcohols (C), diglycerol, triglycerol, polyglycerol, mannitol, sorbitol, erythritol, xylitol or lactitol are preferred. From the perspective of providing an electrolytic capacitor with excellent low ESR characteristics, polyglycerol, sorbitol or mannitol are more preferred.

[0074] Furthermore, in the conductive polymer composition of this embodiment, regarding the content of at least one (C) selected from polyglycerol and sugar alcohol, the total amount of the conductive polymer composition is set to 100% by mass, and is 1 to 50% by mass. From the perspective of providing an electrolytic capacitor with excellent low ESR characteristics, it is more preferably 5 to 50% by mass, more preferably 7 to 50% by mass, and even more preferably 10 to 50% by mass.

[0075] Furthermore, regarding the content of at least one (C) selected from polyglycerol and sugar alcohol, it is preferably 3 to 50 parts by mass relative to 1 part by mass of the above-mentioned polythiophene (A), more preferably 5 to 40 parts by mass, and even more preferably 7 to 30 parts by mass.

[0076] The solvents mentioned above are not particularly limited, and examples include: polyols such as water, ethylene glycol, propylene glycol, or diethylene glycol; cyclic sulfones such as sulfolane; lactones such as γ-butyrolactone; amides such as N-methylacetamide, N,N-dimethylformamide, or N-methyl-2-pyrrolidone; esters such as methyl acetate; carbonate compounds such as propylene carbonate; and 1,4-di(di) ... Alkane ethers; ketones such as methyl ethyl ketone; or polymer solvents such as polyethylene glycol or polypropylene glycol.

[0077] Furthermore, regarding the content of the above-mentioned solvent in the conductive polymer composition of this embodiment, from the perspective of providing an electrolytic capacitor with excellent low ESR characteristics, the total amount of the above-mentioned conductive polymer composition is set to 100% by mass, more preferably 50 to 99% by mass, more preferably 70 to 99% by mass, and even more preferably 80 to 99% by mass.

[0078] The conductive polymer composition of this embodiment may further comprise poly(meth)acrylic acid (D). The poly(meth)acrylic acid (D) described above refers to a polymer formed by polymerizing acrylic monomers and / or methacrylic acid monomers (other copolymers may coexist during polymerization), and is not particularly limited. Examples include acrylic polymers, methacrylic acid polymers, acrylic-methacrylic acid copolymers, acrylic copolymers, or methacrylic acid copolymers.

[0079] In the conductive polymer composition of this embodiment, the weight-average molecular weight of poly(meth)acrylic acid (D) is not particularly limited, but is preferably 100 to 1,000,000, more preferably 1,000 to 500,000, even more preferably 2,000 to 100,000, and particularly preferably 5,000 to 50,000. According to this configuration, it has the advantage of providing an electrolytic capacitor with excellent low ESR characteristics.

[0080] In the conductive polymer composition of this embodiment, regarding the content of the above-mentioned poly(meth)acrylic acid (D), the total amount of the conductive polymer composition in the state containing the poly(meth)acrylic acid (D) is set to 100% by mass, preferably 0.001 to 20% by mass, more preferably 0.01 to 20% by mass from the viewpoint of being able to provide an electrolytic capacitor with excellent low ESR characteristics, and even more preferably 0.1 to 20% by mass.

[0081] Furthermore, regarding the content of the aforementioned poly(meth)acrylic acid (D), it is preferably 0.1 to 10 parts by mass relative to 1 part by mass of the aforementioned polythiophene (A), more preferably 0.2 to 8 parts by mass, and even more preferably 0.3 to 6 parts by mass. According to this configuration, it has the advantage of providing an electrolytic capacitor with excellent low ESR characteristics.

[0082] The conductive polymer composition of this embodiment may further include a compound (E) capable of forming ion pairs with the sulfonic acid or phosphonic acid groups of polythiophene (A).

[0083] The compound (E) that can form ion pairs with the sulfonic acid group or phosphonic acid group of polythiophene (A) is not particularly limited. Examples include alkali metal compounds, ammonia, organic amine compounds, or quaternary ammonium salts. These compounds react with the sulfonic acid group or phosphonic acid group of polythiophene (A) to form alkali metal ion salts, ammonium ion salts, organic ammonium ion salts, or quaternary ammonium ion salts of polythiophene (A).

[0084] The alkali metal compounds mentioned above are not particularly limited, and examples include: alkali metal salt compounds (e.g., lithium chloride, potassium chloride, sodium chloride, rubidium chloride, cesium chloride, lithium bromide, potassium bromide, sodium bromide, rubidium bromide, cesium bromide, etc.) or alkali metal hydroxides (e.g., lithium hydroxide, potassium hydroxide, sodium hydroxide, rubidium hydroxide, cesium hydroxide, etc.).

[0085] By including the above-mentioned alkali metal compound in the conductive polymer composition of this embodiment, an alkali metal ion salt of the above-mentioned polythiophene (A) can be prepared. The alkali metal ion is not particularly limited, and examples include lithium ion, potassium ion, sodium ion, rubidium ion, or cesium ion.

[0086] The organic amine compounds mentioned above are not particularly limited, and examples include: organic primary amine compounds, organic secondary amine compounds, and organic tertiary amine compounds with a total carbon number of 1 to 30. More specifically, examples include: methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, hexylamine, ethanolamine, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 2-amino-2-hydroxymethyl-1,3-propanediol, 1,4-butanediamine, triisobutylamine, triisoamylamine, triisooctylamine, imidazole, N-methylimidazolium, 1,2-dimethylimidazolium, pyridine, methylpyridine, or dimethylpyridine, etc.

[0087] By including the above-mentioned organic amine compound in the conductive polymer composition of this embodiment, the organic amine compound reacts with the above-mentioned polythiophene (A) to form an organic ammonium ion, thereby preparing an organic ammonium ion salt of polythiophene (A). The organic ammonium ion is not particularly limited, and examples include: organic primary ammonium ions, organic secondary ammonium ions, and organic quaternary ammonium ions with a total carbon number of 1 to 30. More specifically, examples include: methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, n-propylammonium, isopropylammonium, n-butylammonium, hexylammonium, 2-hydroxyethylammonium, N,N-dimethyl-N-(2-hydroxyethyl)ammonium, N-methyl-N-(2-hydroxyethyl)ammonium, di... (2-Hydroxyethyl)ammonium, N-methyl-N,N-di(2-hydroxyethyl)ammonium, N,N,N-tris(2-hydroxyethyl)ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, imidazole cation, N-methylimidazolium cation, 1,2-dimethylimidazolium cation, pyridine Ions, methylpyridine Ion or dimethylpyridine ion.

[0088] There are no particular limitations on the quaternary ammonium salts mentioned above. Examples include tetramethylammonium chloride, tetraethylammonium chloride, tetra-n-propylammonium chloride, tetra-n-butylammonium chloride, or tetra-n-hexylammonium chloride.

[0089] By including the aforementioned quaternary ammonium salt in a conductive polymer composition according to one embodiment of the present invention, the quaternary ammonium salt reacts with the aforementioned polythiophene (A) to form a quaternary ammonium ion, thereby preparing a quaternary ammonium ion salt of polythiophene (A). The quaternary ammonium ion is not particularly limited, and examples include tetramethylammonium ion, tetraethylammonium ion, tetra-n-propylammonium ion, tetra-n-butylammonium ion, or tetra-n-hexylammonium ion.

[0090] From the perspective of providing an electrolytic capacitor with excellent low ESR, the compound (E) that can form ion pairs with the sulfonic acid group or phosphonic acid group of polythiophene (A) is preferably an alkali metal hydroxide, ammonia, or an organic primary amine compound, organic secondary amine compound, or organic tertiary amine compound. It should be noted that the organic primary amine compounds, organic secondary amine compounds, and organic tertiary amine compounds with a total carbon number of 1 to 16 mentioned above can be exemplified by: methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, hexylamine, ethanolamine, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisoamylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, methylpyridine, or dimethylpyridine.

[0091] In the case where the conductive polymer composition of this embodiment contains the above-described compound (E), the polythiophene (A) containing at least one structural unit selected from the structural units represented by general formula (1) and general formula (2) interacts with the above-described compound (E) in part or in whole to form a polythiophene (A''') containing at least one structural unit selected from the structural units represented by general formula (1''') and general formula (2''') as described below.

[0092] [Chemical Formula 5]

[0093]

[0094] [In the above general formula (1'''), M represents hydrogen ion, alkali metal ion, ammonium ion, organic ammonium ion, or quaternary ammonium ion. In the above general formulas (1''') and (2'''), the definition and preferred range of R are the same as those shown in the above general formulas (1) and (2).]

[0095] It should be noted that when the conductive polymer composition of this embodiment contains the above-mentioned compound (E), the polythiophene (A') containing at least one structural unit selected from the structural units represented by general formula (1') and general formula (2') interacts with the above-mentioned compound (E) in part or in whole to form a polythiophene (A'''') containing at least one structural unit selected from the structural units represented by the following general formula (1'''') and general formula (2'''').

[0096] [Chemical Formula 6]

[0097]

[0098] In general formulas (1'''') and (2''''), R 2 The definitions and preferred ranges of , m, and n are the same as those of R shown in general formulas (1) and (2) above. 2 The definitions and preferred ranges of , m, and n are the same. M represents hydrogen ion, alkali metal ion, ammonium ion, organic ammonium ion, or quaternary ammonium ion.

[0099] Regarding the alkali metal ions, ammonium ions, organic ammonium ions, and quaternary ammonium ions in M ​​mentioned above, as described above.

[0100] In the conductive polymer composition of this embodiment, regarding the content of the compound (E) that can form ion pairs with the sulfonic acid group or phosphonic acid group of polythiophene (A), the total amount of the conductive polymer composition containing the above-mentioned compound (E) is set to 100% by mass, preferably 0.001 to 20% by mass, more preferably 0.01 to 20% by mass from the viewpoint of being able to provide an electrolytic capacitor with excellent low ESR characteristics, and even more preferably 0.1 to 20% by mass.

[0101] From the perspective of excellent chemical stability, the conductive polymer composition of this embodiment preferably further comprises a conductive polymer (F), which is a composite of poly(3,4-ethylenedioxythiophene derivative) and polyanion containing structural units represented by the following general formula (3).

[0102] [Chemical Formula 7]

[0103]

[0104] In general formula (3), R 3 This refers to a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms with a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms with a substituent.

[0105] The conductive polymer (F) in this embodiment is obtained by oxidative polymerization of a 3,4-ethylenedioxythiophene derivative monomer in water in the presence of a polyanion, the 3,4-ethylenedioxythiophene derivative monomer being equivalent to the monomer used to generate the poly(3,4-ethylenedioxythiophene derivative) containing the structural unit represented by the general formula (3).

[0106] In the above general formula (3), R 3 It represents a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms with a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms with a substituent.

[0107] The alkyl group having 1 to 6 carbon atoms mentioned above is not particularly limited, and examples include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, n-hexyl, 2-ethylbutyl, or cyclohexyl.

[0108] The alkyl group having 1 to 6 carbon atoms mentioned above is not particularly limited, and examples include: hydroxymethyl, trifluoromethyl, aminomethyl, hydroxyethyl, 1,1,1-trifluoroethyl, 2-aminoethyl, 2-hydroxypropyl, 2-hydroxy-3-methoxypropyl, or 2-hydroxycyclohexyl.

[0109] The alkoxy groups with 1 to 6 carbon atoms mentioned above are not particularly limited, and examples include: methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, isopentoxy, neopentoxy, tert-pentoxy, cyclopentoxy, n-hexyloxy, 2-ethylbutoxy, or cyclohexyloxy.

[0110] The alkoxy groups having 1 to 6 carbon atoms mentioned above are not particularly limited, and examples include: hydroxymethoxy, trifluoromethoxy, aminomethoxy, hydroxyethoxy, 1,1,1-trifluoroethoxy, 2-aminoethoxy, 2-hydroxypropoxy, 2-hydroxy-3-methoxypropoxy, or 2-hydroxycyclohexyloxy, etc.

[0111] Regarding R 3 From the perspective of excellent moisture resistance, it is preferably selected from any one of hydrogen atom, methoxy, ethoxy, propoxy, butoxy, and hydroxymethyl, more preferably hydrogen atom or hydroxymethyl, and even more preferably hydrogen atom.

[0112] The 3,4-ethylenedioxythiophene derivative monomers that are the source of the structural units represented by the above general formula (3) can be used alone or in combination for polymerization. More preferably, 3,4-ethylenedioxythiophene can be used alone.

[0113] The polyanion used is not particularly limited, and examples include polystyrene sulfonic acid, polyvinyl sulfonic acid, or polyallyl sulfonic acid, or their metal salts, ammonium salts, or amine salts. Among these, polystyrene sulfonic acid is preferred from the perspective of providing electrolytic capacitors with excellent low ESR characteristics.

[0114] Regarding the conductive polymer (F), from the perspective of providing an electrolytic capacitor with excellent low ESR characteristics, a composite formed of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS) (hereinafter referred to as "PEDOT:PSS") is preferred, and commercially available products can also be used for PEDOT:PSS.

[0115] Furthermore, in the conductive polymer composition of this embodiment, the content of the conductive polymer (F) is preferably 0.001 to 20 parts by mass relative to 1 part by mass of the polythiophene (A), more preferably 0.1 to 20 parts by mass, and even more preferably 1 to 20 parts by mass.

[0116] The conductive polymer composition of this embodiment may also contain other components (G) besides those described above.

[0117] Other than those mentioned above (G) are not particularly limited, and examples include adhesives or surfactants.

[0118] The adhesives mentioned above are not particularly limited, and examples include: polyvinyl alcohol, polyvinylpyrrolidone, cellulose, water-soluble polyester resin compounds, water-soluble polyurethane resin compounds, or mixtures of organic acids having two or more carboxyl groups.

[0119] Examples of the aforementioned water-soluble polyester resin compounds include polyethylene terephthalate (PET) or polypropylene terephthalate (PPD). This water-soluble polyester resin compound can be either self-emulsifying or reinforced emulsifying; from the viewpoint of water resistance and solvent resistance, a self-emulsifying water-soluble polyester resin compound is preferred.

[0120] The aforementioned water-soluble polyester resin compounds, such as those manufactured by Toyobo Co., Ltd. (trade name: Vylonal), Takamatsu Oil & Fat Co., Ltd. (trade name: Pesresin), Muyo Chemical Co., Ltd. (trade name: Plascoat), Toa Synthetic Co., Ltd. (trade name: Aron Melt), Takamatsu Oil & Fat Co., Ltd. (trade name: Pesresin A), and DIC Co., Ltd. (trade name: Watersol), are readily available through commercial channels.

[0121] The above-mentioned water-soluble polyester resin compounds can be used alone or in combination of two or more.

[0122] The aforementioned water-soluble polyurethane resin compounds are mainly used in industrial applications in the form of urethane resin emulsions. They can be self-emulsifying or reinforced emulsifying. From the viewpoint of water resistance and solvent resistance, self-emulsifying water-soluble polyurethane resin compounds are preferred. Examples of self-emulsifying compounds include anionic, cationic, or nonionic types; any type is acceptable. Furthermore, there are no particular limitations on the water-soluble polyurethane resin compound; examples include polyether, polyester, or polycarbonate types.

[0123] For water-soluble polyurethane resin compounds, such as those manufactured by Sanyo Chemical Industries, Ltd. (trade names: UCOAT, Permarin, UPRENE), manufactured by Kusunoki Chemical Industries, Ltd. (trade name: NeoRez), manufactured by ADEKA Corporation (trade name: ADEKA Bontighter), manufactured by Meisei Chemical Industries, Ltd. (trade name: Pascol), and manufactured by DIC Corporation (trade name: Hydrun), they can be easily obtained through commercial channels.

[0124] The above-mentioned water-soluble polyurethane resin compounds can be used alone or in combination of two or more.

[0125] The organic acids having two or more carboxyl groups mentioned above are not particularly limited, and examples include adipic acid or phthalic acid.

[0126] The surfactants mentioned above are not particularly limited, and for example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, fluorinated surfactants or organosilicon surfactants can be used, and more preferably, at least one selected from nonionic surfactants and amphoteric surfactants can be used.

[0127] The anionic surfactants mentioned above are not particularly limited, and examples include sodium lauryl sulfate or sodium dodecylbenzene sulfonate.

[0128] There are no particular limitations on the aforementioned cationic surfactants; commercially available products can be used, or commonly known cationic surfactants can be manufactured separately for use.

[0129] The above-mentioned nonionic surfactants are not particularly limited, and examples include: polyethylene glycol type surfactants, alkynyl glycol type surfactants, polyol type surfactants, or high molecular weight nonionic surfactants.

[0130] The polyethylene glycol-type surfactants mentioned above are not particularly limited, and examples include: higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, fatty acid ethylene oxide adducts, polyol fatty acid ester ethylene oxide adducts, higher alkylamine ethylene oxide adducts, oleic acid ethylene oxide adducts, or polypropylene glycol ethylene oxide adducts, etc.

[0131] There are no particular limitations on the aforementioned acetylenol-type surfactants; examples include 2,4,7,9-tetramethyl-5-decyn-4,7-diol, Surfynol (manufactured by Air Products), and Olefin (manufactured by Nissin Chemical Industry Co., Ltd.).

[0132] The polyol-type surfactants mentioned above are not particularly limited, and examples include: fatty acid esters of glycerol, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol and dehydrated sorbitol, fatty acid esters of sucrose, and fatty acid amides of high-alcohol alkyl ethers or alkanolamines.

[0133] The aforementioned amphoteric surfactants are not particularly limited; for example, betaine-type amphoteric surfactants can be cited. As for betaine-type amphoteric surfactants, there are no particular limitations; for example, alkyl dimethyl betaine, lauryl dimethyl betaine, stearyl dimethyl betaine, or lauryl dihydroxyethyl betaine, etc., can be cited.

[0134] As for the aforementioned fluorinated surfactants, there are no particular limitations as long as they contain a perfluoroalkyl group. Examples include Plascoat RY-2, perfluoroalkanes, perfluoroalkyl carboxylic acids, perfluoroalkyl sulfonic acids, or perfluoroalkyl ethylene oxide adducts.

[0135] The aforementioned organosilicon surfactants are not particularly limited, and examples include: polyether-modified polydimethylsiloxane, polyether ester-modified polydimethylsiloxane, hydroxyl-containing polyether-modified polydimethylsiloxane, acrylic polyether-modified polydimethylsiloxane, methacrylic polyether-modified polydimethylsiloxane, acrylic polyester-modified polydimethylsiloxane, methacrylic polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, organosilicon-modified acrylic compounds, or organosilicon-modified methacrylic compounds, etc.

[0136] It should be noted that fluorinated surfactants or silicone surfactants are effective as leveling agents in improving the flatness of coatings.

[0137] In the conductive polymer composition of this embodiment, regarding the content of the above-mentioned component (G), the total amount of the conductive polymer composition containing the above-mentioned component (G) is set to 100% by mass, preferably 0.001 to 20% by mass, more preferably 0.01 to 15% by mass from the viewpoint of excellent operability, and even more preferably 0.1 to 10% by mass.

[0138] It should be noted that the pH of the conductive polymer composition in this embodiment is not particularly limited, but is preferably 1.5 to 5.0, more preferably 2.0 to 4.0, even more preferably 2.5 to 3.5, further preferably 2.75 to 3.25, and particularly preferably 3.0. According to this configuration, it has the advantage of providing an electrolytic capacitor exhibiting low ESR characteristics. It should be noted that the pH of the conductive polymer composition can be controlled by the type and content of the compounds (E) that can form ion pairs with sulfonic acid groups or phosphonic acid groups described above.

[0139] The method for preparing the conductive polymer composition of this embodiment is not particularly limited. For example, it can be a method of mixing a solution or solid of the above-mentioned polythiophene (A), a nanostructure material (B), at least one selected from polyglycerol and sugar alcohol (C), a solvent, and poly(meth)acrylic acid (D) used as needed, a compound (E) capable of forming ion pairs with the sulfonic acid group or phosphonic acid group of polythiophene (A), a conductive polymer (F), and / or component (G), and homogenizing by stirring or the like.

[0140] Here, the temperature during mixing is not particularly limited; for example, it can be carried out at room temperature to heated temperature, preferably 0~100°C.

[0141] There are no particular restrictions on the atmosphere in which the mixture is mixed; it can be in the atmosphere or in an inert gas.

[0142] When mixing the conductive polymer composition of this embodiment, a general mixing and dissolving operation method using a stir bar or stirring blades can be employed. Alternatively, mixing can be performed by ultrasonic irradiation or homogenization treatment (e.g., using a mechanical homogenizer, ultrasonic homogenizer, high-pressure homogenizer, etc.). In the case of homogenization treatment, it is preferable to perform the homogenization while cooling to prevent thermal degradation of the polymer.

[0143] The concentration of the conductive polymer composition in this embodiment can be adjusted by the mixing ratio or by concentration after mixing. The concentration method can be the removal of solvent by distillation under reduced pressure or by using an ultrafiltration membrane.

[0144] The content of polythiophene (A) in the conductive polymer composition of this embodiment is not particularly limited as long as it is 0.01 to 10% by mass. It should be noted that for conductive polymer compositions containing polythiophene (A), nanostructured materials (B), and at least one (C) selected from polyglycerol and sugar alcohols, drying / dehydration is performed after coating. Therefore, by setting the content within the above range, a good uniform film can be obtained.

[0145] The particle size of the solid component in the conductive polymer composition of this embodiment is not particularly limited, but smaller particle size results in better water solubility, and is preferred from the viewpoint of conductivity and the formation of a uniform film during film formation. For example, when the concentration of the solid component in the conductive polymer composition prepared at room temperature or under heating is 10% by mass or less, the particle size (D50) of the solid component is preferably 0.02 μm or less.

[0146] The viscosity (at 20°C) of the conductive polymer composition of this embodiment is preferably 200 mPa·s or less, more preferably 150 mPa·s or less, and even more preferably 100 mPa·s or less.

[0147] The conductive polymer film of this embodiment can be formed using the conductive polymer composition of this embodiment. The method (manufacturing method) for forming the conductive polymer film of this embodiment is not particularly limited; for example, a method including a step of coating the conductive polymer composition of this embodiment onto a substrate and drying it can be cited.

[0148] The dry atmosphere can be any atmosphere, including the atmosphere, an inert gas, a vacuum, or a reduced pressure environment. From the perspective of suppressing the degradation of the polymer film, an inert gas such as nitrogen or argon is preferred.

[0149] The substrates mentioned above are not particularly limited, and examples include: glass, plastic, polyester, polyacrylate, polycarbonate, metal oxide, ceramic or resist substrate, etc.

[0150] The coating methods described above are not particularly limited, and examples include: casting, dipping, bar coating, roller coating, gravure coating, aniline printing, spraying, spin coating, or inkjet printing.

[0151] The drying temperature of the coating is not particularly limited as long as it is the temperature at which a uniform conductive film can be obtained. Preferably, it is in the range of room temperature to 300°C, more preferably in the range of room temperature to 250°C, and even more preferably in the range of room temperature to 200°C. It should be noted that, in this specification, room temperature refers to 15~25°C.

[0152] The thickness of the coating is not particularly limited, but is preferably 10 mm. -2 ~10 2The range is μm. The surface resistivity of the resulting coating is not particularly limited, but is preferably 1 to 10 μm. 9 Surface resistivity in the range of Ω / □.

[0153] The conductivity of the conductive polymer film obtained in this embodiment is not particularly limited, but the conductivity in the film state is preferably 10 S / cm or higher.

[0154] The conductive polymer film of this embodiment can be used, for example, as an antistatic agent, a solid electrolyte for electrolytic capacitors, a conductive coating, an electrochromic element, an electrode material, a thermoelectric conversion material, a transparent conductive film, a chemical sensor, or an actuator. In particular, it is very useful as a solid electrolyte for electrolytic capacitors. When the conductive polymer film of this embodiment is used in an electrolytic capacitor, an electrolytic capacitor with excellent low ESR characteristics while maintaining high capacitance can be provided.

[0155] Furthermore, the conductive polymer film of this embodiment can provide long-life electrolytic capacitors, thus contributing to improved energy efficiency. This, in turn, contributes to the achievement of the Sustainable Development Goals (SDGs).

[0156] As a method for manufacturing the electrolytic capacitor of this embodiment, one example includes a step of covering the surface of the dielectric oxide film of an anode body to which a dielectric oxide film is formed with the conductive polymer composition of this embodiment and then heating and drying it. More specifically, a method for manufacturing the electrolytic capacitor of this embodiment may include a step of immersing an element comprising an anode body and a cathode in the conductive polymer composition of this embodiment and then heating and drying it.

[0157] The electrolytic capacitor used in this embodiment is not particularly limited; for example, it can be an aluminum wound electrolytic capacitor, an aluminum laminated electrolytic capacitor, or a tantalum electrolytic capacitor.

[0158] The electrolyte in this embodiment is not particularly limited. For example, it can be an electrolyte containing a solvent and an alkaline component dissolved in the solvent.

[0159] In this embodiment, the anode body preferably comprises a dielectric oxide film (dielectric layer) and an anode. Alternatively, the dielectric layer can be considered to be made of an oxide film.

[0160] In this embodiment, there is no particular limitation on the anode, but from the viewpoint of easily forming a dielectric layer, it is preferably selected from one or more of aluminum, tantalum, niobium and titanium, and more preferably made of aluminum.

[0161] In this embodiment, the oxide film constituting the dielectric layer is preferably formed by oxidizing the surface of the anode. The method for forming this oxide film on the surface of the anode (i.e., the method for manufacturing the anode body) is not particularly limited, and methods such as oxidizing the anode by applying a voltage in a buffer solution are also possible.

[0162] In this embodiment, there is no particular limitation on the cathode, but from the viewpoint of easily forming a dielectric layer, it is preferably selected from one or more of aluminum, silver, tantalum, niobium and titanium, and more preferably made of aluminum.

[0163] The drying temperature in the method for manufacturing the electrolytic capacitor of this embodiment can be referenced from the description of the drying temperature of the coating in the method (manufacturing method) for forming the conductive polymer film of this embodiment.

[0164] Furthermore, the hybrid capacitor in this embodiment is obtained, for example, by obtaining a solid electrolytic capacitor using the method described above, and then immersing the solid electrolytic capacitor in an electrolyte. In other words, the manufacturing method of the electrolytic capacitor in this embodiment includes: a step of covering the surface of the dielectric oxide film of an anode body to which the dielectric oxide film is formed with the conductive polymer composition of this embodiment and then heating and drying it; and a further step of impregnating it with electrolyte and then heating and drying it again.

[0165] [Summarize]

[0166] The inventors conducted repeated and in-depth research and found that the following conductive polymer composition can solve the problems of the present invention, thereby completing the present invention.

[0167] That is, one aspect of the present invention relates to a conductive polymer composition, a conductive polymer film, and an electrolytic capacitor using the conductive polymer composition, as shown below.

[0168] [1] A conductive polymer composition comprising:

[0169] Polythiophene (A) 0.01~10% by mass containing at least one structural unit selected from the structural units represented by the following general formula (1) and the structural units represented by the following general formula (2).

[0170] Nanostructured materials (B) 0.001~10% by mass

[0171] Selected from at least one of polyglycerol and sugar alcohols (C) 1-50% by mass, and

[0172] solvent,

[0173] [Chemical Formula 8]

[0174]

[0175] In the above general formula (1), M + In general formulas (1) and (2) above, R represents an organic group having a total number of 1 to 18 carbon atoms having at least one substituent selected from sulfonic acid group and phosphonic acid group.

[0176] [2] According to the conductive polymer composition described in [1], wherein,

[0177] The aforementioned nanostructure material (B) is selected from at least one of cellulose nanofibers, single-layer carbon nanotubes, double-layer carbon nanotubes, and multilayer carbon nanotubes.

[0178] [3] The conductive polymer composition according to [1] or [2], wherein,

[0179] The aforementioned nanostructure material (B) is cellulose nanofiber or monolayer carbon nanotube.

[0180] [4] The conductive polymer composition according to any one of [1] to [3], wherein,

[0181] The sugar alcohols mentioned above are sorbitol, mannitol, erythritol, xylitol, or lactitol.

[0182] [5] The conductive polymer composition according to any one of [1] to [4], wherein,

[0183] It further contains 0.001 to 20% by mass of poly(meth)acrylic acid (D).

[0184] [6] The conductive polymer composition according to any one of [1] to [5], wherein,

[0185] It further contains 0.001 to 20 by mass of a compound (E) capable of forming an ion pair with the sulfonic acid group or phosphonic acid group of polythiophene (A).

[0186] [7] The conductive polymer composition according to any one of [1] to [6], wherein,

[0187] The content of the nanostructure material (B) is 0.01 to 5 parts by mass relative to 1 part by mass of the above-mentioned polythiophene (A).

[0188] [8] The conductive polymer composition according to any one of [1] to [7], wherein,

[0189] The content of at least one of polyglycerol and sugar alcohol (C) is 3 to 50 parts by weight relative to 1 part by weight of polythiophene (A) mentioned above.

[0190] [9] According to the conductive polymer composition described in [5], wherein,

[0191] The content of poly(meth)acrylic acid (D) is 0.1 to 10 parts by weight relative to 1 part by weight of polythiophene (A).

[0192]

[10] The conductive polymer composition according to any one of [1] to [9], wherein,

[0193] The product further comprises a conductive polymer (F), which is a composite of poly(3,4-ethylenedioxythiophene derivative) and polyanionic polymer containing structural units represented by the following general formula (3). The content of the conductive polymer (F) is 0.001 to 20 parts by mass relative to 1 part by mass of the polythiophene (A).

[0194] [Chemical Formula 9]

[0195]

[0196] In the formula, R 3 It represents a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms with a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms with a substituent.

[0197]

[11] According to the conductive polymer composition of

[10] , wherein,

[0198] R 3 It is a hydrogen atom.

[0199]

[12] The conductive polymer composition according to

[10] or

[11] , wherein,

[0200] The conductive polymer (F) mentioned above is PEDOT:PSS.

[0201]

[13] A method for manufacturing an electrolytic capacitor, the method comprising:

[0202] The process of covering the surface of the dielectric oxide film of the anode body with the dielectric oxide film formed thereon with the conductive polymer composition described in any one of [1] to

[12] and then heating and drying it.

[0203]

[14] A method for manufacturing an electrolytic capacitor, the method comprising:

[0204] The process of covering the surface of the dielectric oxide film of the anode body to which the dielectric oxide film is formed with the conductive polymer composition described in any one of [1] to

[12] and then heating and drying it; and

[0205] The next step is to further impregnate the electrolyte with it and then heat and dry it again.

[0206] [Additional Notes]

[0207] This invention is not limited to the embodiments described above. Various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the disclosed technical means in different embodiments are also included in the scope of the technology of this invention.

[0208] Example

[0209] The present invention will now be described in detail through examples. However, the present invention is not to be construed as being limited thereto.

[0210] It should be noted that the analytical instruments and measurement methods used in this embodiment are listed below.

[0211] [Conductivity determination of polythiophene (A)]

[0212] 0.5 ml of an aqueous solution containing PEDOT-MPS (equivalent to polythiophene (A) of one aspect of the present invention) was coated onto a 25 mm square alkali-free glass plate. The plate was heated at 60 °C for 30 minutes on a hot plate under atmospheric conditions, and then further heated at 200 °C for 60 minutes to obtain a conductive polymer film.

[0213] For the aforementioned conductive polymer film, cuts were made at intervals of 6.25 mm in the x-direction and 6.25 mm in the y-direction to expose the glass portion, and the film thickness was measured at nine measurement sites in an atmosphere of 25°C and 50% RH. A DEKTAK XT sensor manufactured by BRUKER Corporation was used as the measuring apparatus. Furthermore, the surface resistivity at the aforementioned nine measurement sites was measured in an atmosphere of 25°C and 50% RH. A Loresta GP MCP-T600 surface resistivity meter manufactured by Mitsubishi Chemical Corporation was used as the measuring apparatus, with the measuring probe as the ASP.

[0214] The conductivity was calculated based on the film thickness and surface resistivity of the conductive polymer film measured by the above-mentioned method, and using the following formula.

[0215] Conductivity [S / cm] = 10 4 / (Surface resistivity [Ω / □] × Film thickness [μm])

[0216] [Fabrication of Solid Electrolytic Capacitors]

[0217] Aluminum foil was soldered to a portion of etched aluminum foil with a thickness of 100 μm, and a lead wire (anode) was installed. The etched aluminum foil was immersed in an aqueous solution of 0.2 wt% ammonium dihydrogen phosphate at a liquid temperature of 80 °C, and a DC voltage of 130 V was applied for 20 minutes, forming a dielectric layer (anode body) made of aluminum oxide (i.e., an oxide film of aluminum) on the surface of the anode.

[0218] A 50 μm thick aluminum foil with leads and an etched finish was used as the cathode. A diaphragm made of insulating paper was sandwiched between the anode and the cathode, and the foil was wound to create a wound element. Next, the wound element was immersed in the conductive polymer composition described later and removed, then dried at 150°C for 30 minutes to create an unsealed solid electrolytic capacitor element.

[0219] [Making a Hybrid Capacitor]

[0220] The solid electrolytic capacitor element produced by the above method is impregnated with ethylene glycol to obtain an unsealed hybrid capacitor element.

[0221] [Characteristic Measurement of Capacitor Components]

[0222] Device: LCR Meter IM3536 manufactured by Hioki Electric Co., Ltd.

[0223] Regarding the characteristics of the solid electrolytic capacitor element and the hybrid capacitor element produced by the above method, the initial capacitance [μF] at 120 Hz and the initial ESR [mΩ] at 100 kHz were evaluated using the above apparatus.

[0224] Here, regarding "solid electrolytic capacitors", if the initial capacitance [μF] at 120Hz is 100μF or higher, the "solid electrolytic capacitor is considered to have high capacitance".

[0225] In addition, regarding "solid electrolytic capacitors", if the initial ESR [mΩ] at 100kHz is below 15.0mΩ, it is determined that "solid electrolytic capacitors exhibit low ESR characteristics".

[0226] In addition, the capacitance [μF] at 120 Hz and the ESR [mΩ] at 100 kHz of the above-mentioned "hybrid capacitor element" were also evaluated after being placed at 150°C for 500 hours.

[0227] Furthermore, the inventors discovered that when the capacitance [μF] at 120Hz and the ESR [mΩ] at 100kHz of the "hybrid capacitor element" after being placed at 150°C for 500 hours are good values, it can maintain high capacitance and low ESR characteristics for a long time (several thousand hours) at temperatures lower than 150°C. Therefore, in this embodiment, when the ESR [mΩ] at 100kHz of the "hybrid capacitor element" after being placed at 150°C for 500 hours, as measured by the above method, is 20mΩ or less, or the ESR change rate (R / R0) is 1.70 or less, it is determined that "the hybrid capacitor can maintain low ESR characteristics for a long time." Additionally, when the capacitance [μF] at 120Hz of the "hybrid capacitor element" after being placed at 150°C for 500 hours, as measured by the above method, is 100μF or more, it is determined that "the hybrid capacitor can maintain high capacitance for a long time."

[0228] [Dissolution test of conductive polymer film into ethylene glycol]

[0229] 0.1 ml of the conductive polymer composition prepared in the examples described later was coated onto a 10 mm square alkali-free glass plate. The plate was heated at 60°C for 30 minutes on a hot plate in atmospheric conditions, and then further heated at 150°C for 30 minutes to obtain a conductive polymer film. The resulting film was then immersed in ethylene glycol, heated in an oven at 150°C for 1 hour, and removed. The presence or absence of dissolution of the conductive polymer film into the ethylene glycol was confirmed by visual inspection.

[0230] If ethylene glycol appears black or blue due to PEDOT-MPS, it indicates that the aforementioned conductive polymer film has dissolved. Such conductive polymer films have poor ethylene glycol resistance (undesirable).

[0231] If the ethylene glycol remains colorless after heating, it indicates that no conductive polymer film has dissolved. Such a conductive polymer film exhibits excellent (good) ethylene glycol resistance.

[0232] Synthesis example 1

[0233] Based on Synthesis Example 1 and Synthesis Example 2 of the publicly known document (Japanese Patent Application Publication No. 2019-196443), poly(3-[(2,3-dihydrothiophene[3,4-b]-[1,4]di) was prepared. An aqueous solution of [[2-yl]methoxy]-1-methyl-1-propanesulfonic acid (hereinafter referred to as "PEDOT-MPS"). PEDOT-MPS is a polymer comprising the structural units represented by the following formulas (5) and (6), corresponding to polythiophene (A) in one embodiment of the present invention. The concentration of polythiophene (A) contained in the aqueous solution is 0.74% by mass. In addition, the aqueous solution contains 44 ppm of iron ions and 12 ppm of sodium ions (relative to the polymer). The conductivity of the above-mentioned PEDOT-MPS is 342 S / cm.

[0234] [Chemical Formula 10]

[0235]

[0236] Example 1

[0237] (Preparation of conductive polymer compositions)

[0238] The aqueous solution of PEDOT-MPS obtained in Synthesis Example 1 was dehydrated under reduced pressure to prepare an aqueous solution containing 2.10% by mass of PEDOT-MPS. To 9.524 g of the aqueous solution containing 2.10% by mass of PEDOT-MPS, 5.00 g of 0.4% monolayer carbon nanotube aqueous dispersion (WPC-040 manufactured by Kusunoki Chemicals), 2.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), 1.8 g of sorbitol, and 1.68 g of water were added and stirred. Next, 0.06 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0239] Example 2

[0240] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 5.00 g of a 0.4% monolayer carbon nanotube aqueous dispersion (WPC-040 manufactured by Kusumoto Kasei), 1.33 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 manufactured by Nippon Shokubai), 2.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical), 1.8 g of sorbitol, and 0.343 g of water were added and stirred. Next, 0.06 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0241] Example 3

[0242] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 2.0 g of polyglycerol (Sakamoto Pharmaceutical Co., Ltd., polyglycerol #310), 1.8 g of sorbitol, and 6.656 g of water were added and stirred. Next, 0.06 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0243] Example 4

[0244] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 1.33 g of a 45% aqueous solution of polyacrylic acid (Nippon Shokubai Corporation AQUALIC HL415), 2.0 g of polyglycerol (Sakamoto Pharmaceutical Corporation Polyglycerol #310), 1.8 g of sorbitol, and 5.323 g of water were added and stirred. Next, 0.06 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0245] Example 5

[0246] To 9.524 g of an aqueous solution containing 2.10% PEDOT-MPS, 0.02 g of multilayer carbon nanotubes (Tokyo Kasei Corporation), 2.0 g of polyglycerol (Sakamoto Pharmaceutical Co., Ltd., polyglycerol #310), 1.8 g of sorbitol, and 6.656 g of water were added and stirred. Next, 0.06 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0247] Example 6

[0248] To 9.524 g of an aqueous solution containing 2.10% PEDOT-MPS, 5.00 g of a 0.4% monolayer carbon nanotube aqueous dispersion (WPC-040, manufactured by Kusumoto Kasei), 1.33 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415, manufactured by Nippon Shokubai), 2.0 g of polyglycerol (Polyglycerol #310, manufactured by Sakamoto Pharmaceutical), 1.8 g of sorbitol, and 0.343 g of water were added and stirred. Next, 0.06 g of monoethanolamine was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of monoethanolamine was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0249] Example 7

[0250] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 5.00 g of a 0.4% monolayer carbon nanotube aqueous dispersion (WPC-040 manufactured by Kusunoki Chemicals), 2.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), 1.8 g of mannitol, and 1.68 g of water were added and stirred. Next, 0.06 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0251] Example 8

[0252] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 2.0 g of polyglycerol (Sakamoto Pharmaceutical Co., Ltd., polyglycerol #310), 1.8 g of sorbitol, and 1.656 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0253] Example 9

[0254] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 1.33 g of a 45% polyacrylic acid aqueous solution (Nippon Shokubai Corporation AQUALIC HL415), 2.0 g of polyglycerol (Sakamoto Pharmaceutical Corporation Polyglycerol #310), 1.8 g of sorbitol, and 0.323 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0255] Example 10

[0256] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 1.33 g of a 45% polyacrylic acid aqueous solution (Nippon Shokubai Corporation AQUALIC HL415), 2.0 g of polyglycerol (Sakamoto Pharmaceutical Corporation Polyglycerol #310), and 2.123 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0257] Example 11

[0258] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 1.33 g of a 45% polyacrylic acid aqueous solution (Nippon Shokubai Corporation AQUALIC HL415), 4.0 g of sorbitol, and 0.123 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0259] Example 12

[0260] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 1.33 g of a 45% polyacrylic acid aqueous solution (Nippon Shokubai Corporation AQUALIC HL415), 2.0 g of sorbitol, 2.0 g of mannitol, and 0.123 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0261] Example 13

[0262] Using the conductive polymer composition obtained in Example 2, a conductive polymer film was prepared according to the method described above for the [Dissolution Test of Conductive Polymer Film into Ethylene Glycol], and a dissolution test into ethylene glycol was conducted. The evaluation results are shown in Table 4.

[0263] Example 14

[0264] Using the conductive polymer composition obtained in Example 9, a conductive polymer film was prepared according to the method described above for the [Dissolution Test of Conductive Polymer Film into Ethylene Glycol], and a dissolution test into ethylene glycol was conducted. The evaluation results are shown in Table 4.

[0265] Comparative Example 1

[0266] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 10.476 g of water was added and the mixture was stirred. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0267] Comparative Example 2

[0268] To 9.524 g of an aqueous solution containing 2.10% PEDOT-MPS, 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 1.8 g of sorbitol, and 8.438 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0269] Comparative Example 3

[0270] To 9.524 g of an aqueous solution containing 2.10% by mass of PEDOT-MPS, 0.02 g of monolayer carbon nanotubes (Tokyo Kasei Corporation), 5.00 g of a 1.2% PEDOT:PSS aqueous dispersion, 1.33 g of a 45% polyacrylic acid aqueous solution (Nippon Shokubai Corporation AQUALIC HL415), and 4.123 g of water were added and stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer composition with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Using the above conductive polymer composition, solid electrolytic capacitor elements and hybrid capacitor elements were fabricated according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0271] Comparative Example 4

[0272] 1.67 g of water was added to 8.33 g of a 1.2% by mass aqueous dispersion of PEDOT:PSS (equivalent to conductive polymer (F)) and the mixture was stirred. Next, 0.03 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the resulting mixture and stirred to obtain a conductive polymer aqueous dispersion with pH=3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT:PSS. Solid electrolytic capacitor elements and hybrid capacitor elements were fabricated using the above conductive polymer aqueous dispersion according to the above method, and their characteristics were evaluated. The evaluation results are shown in Table 2 or Table 3.

[0273] Comparative Example 5

[0274] To 13.33 g of a 1.2% by mass aqueous dispersion of PEDOT:PSS (equivalent to conductive polymer (F)), 5.00 g of a 0.4% aqueous dispersion of monolayer carbon nanotubes (WPC-040 manufactured by Kusunoki Chemicals) and 1.67 g of water were added and stirred. The resulting mixture agglomerated and could not be used to fabricate a solid electrolytic capacitor.

[0275] Comparative Example 6

[0276] Using the conductive polymer composition obtained in Comparative Example 2, a conductive polymer film was prepared according to the method described above for the [Dissolution Test of Conductive Polymer Film into Ethylene Glycol], and a dissolution test into ethylene glycol was conducted. The evaluation results are shown in Table 4.

[0277] Table 1 shows the composition of Examples 1 to 12 and Comparative Examples 1 to 5.

[0278]

[0279]

[0280]

[0281] Based on the results shown in Table 2, Examples 1 to 12 demonstrate the effectiveness of solid electrolytic capacitors that provide high capacitance and exhibit low ESR characteristics.

[0282] Comparative Examples 1 through 4 failed to achieve both the high capacitance and low ESR characteristics of solid electrolytic capacitors. Furthermore, Comparative Example 5 exhibited agglomeration, making it impossible to manufacture a solid electrolytic capacitor.

[0283] Furthermore, according to the results shown in Table 3, Examples 1 to 12 demonstrated the ability to suppress the decrease in capacitance and the increase in ESR of the hybrid capacitor after being placed at 150°C for 500 hours.

[0284] Furthermore, based on the results shown in Table 4, Examples 13 and 14 demonstrate the effect of providing a conductive polymer film that suppresses the dissolution of ethylene glycol, the electrolyte used as a mixed capacitor.

[0285] One reason for suppressing the ESR increase of the aforementioned hybrid capacitor during heat resistance testing is the inhibitory effect of the conductive polymer film on dissolution into the electrolyte.

[0286] Industrial applicability

[0287] As described above, if the conductive polymer composition of this embodiment is used, an electrolytic capacitor with high capacitance and low ESR characteristics can be provided compared with the case where conventional conductive polymer compositions are used.

Claims

1. A conductive polymer composition comprising: Polythiophene (A) 0.01~10% by mass containing at least one structural unit selected from the structural units represented by the following general formula (1) and the structural units represented by the following general formula (2). Nanostructured materials (B) 0.001~10% by mass Selected from at least one of polyglycerol and sugar alcohols (C) 1-50% by mass, and solvent, , In the general formula (1), M + The symbol represents a hydrogen ion. In the general formulas (1) and (2), R represents an organic group having a total number of 1 to 18 carbon atoms having at least one substituent selected from sulfonic acid group and phosphonic acid group.

2. The conductive polymer composition according to claim 1, wherein, The nanostructure material (B) is selected from at least one of cellulose nanofibers, single-layer carbon nanotubes, double-layer carbon nanotubes, and multilayer carbon nanotubes.

3. The conductive polymer composition according to claim 1, wherein, The nanostructure material (B) is cellulose nanofiber or single-layer carbon nanotube.

4. The conductive polymer composition according to claim 1, wherein, The sugar alcohol is sorbitol, mannitol, erythritol, xylitol, or lactitol.

5. The conductive polymer composition according to claim 1, wherein, It further contains 0.001 to 20% by mass of poly(meth)acrylic acid (D).

6. The conductive polymer composition according to claim 1, wherein, It further contains 0.001 to 20 by mass of a compound (E) capable of forming an ion pair with the sulfonic acid group or phosphonic acid group of polythiophene (A).

7. The conductive polymer composition according to claim 1, wherein, The content of the nanostructure material (B) is 0.01 to 5 parts by mass relative to 1 part by mass of the polythiophene (A).

8. The conductive polymer composition according to claim 1, wherein, The content of at least one (C) selected from polyglycerol and sugar alcohol is 3 to 50 parts by weight relative to 1 part by weight of polythiophene (A).

9. The conductive polymer composition according to claim 5, wherein, The content of poly(meth)acrylic acid (D) is 0.1 to 10 parts by weight relative to 1 part by weight of polythiophene (A).

10. The conductive polymer composition according to claim 1, wherein, The product further comprises a conductive polymer (F), which is a complex of poly(3,4-ethylenedioxythiophene derivative) and polyanionic polymer containing structural units represented by the following general formula (3), wherein the content of the conductive polymer (F) is 0.001 to 20 parts by mass relative to 1 part by mass of the polythiophene (A). , In the formula, R 3 It represents a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms with a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms with a substituent.

11. The conductive polymer composition according to claim 10, wherein, R 3 It is a hydrogen atom.

12. The conductive polymer composition according to claim 10, wherein, The conductive polymer (F) is PEDOT:PSS.

13. A method for manufacturing an electrolytic capacitor, comprising: The process of covering the surface of the dielectric oxide film of an anode body with a dielectric oxide film formed thereon with the conductive polymer composition according to any one of claims 1 to 12 and then heating and drying it.

14. A method for manufacturing an electrolytic capacitor, comprising: The steps of coating the surface of the dielectric oxide film of an anode having a dielectric oxide film formed by the conductive polymer composition according to any one of claims 1 to 12 with the mixture and then heating and drying it; and The process involves further impregnation with electrolyte and subsequent heating and drying.

Citation Information

Patent Citations

  • Artificial dialyser

    JP1998000233A

  • Aqueous conductive polymer solution and conductive polymer film

    JP2019196443A

  • Conductive polymer composition, and conductive polymer film

    JP2022142739A